"Black blokes who spoke like East-Enders": Nation, race and hooliganism in Cass Pennant's Cass. Issue 1 (2nd January 2016) - Ramos Gay, Ignacio
Abstract: Cass Pennant's autobiography Cass revolves around his days as one of the top men of West Ham's ill-reputed InterCity Firm (ICF). As a narrative that spans over 40 years, it intertwines Pennant's personal account with the rise and fall of hooliganism in Britain during the late 1970s and early 1980s. Pennant was born in East London and fostered by a white, working-class family; his narrative is a detailed introspective description of his progress from his beginnings as a black hooligan to his eventual self-perception as a black Jamaican. This article analyses the manner in which Pennant assimilates, conceptualizes and instrumentalizes his blackness for different purposes throughout his life journey, and how, looking back, he comes to terms with his shifting understanding of race as an inherent part of the progress of his Bildungsroman. It concludes with a discussion of the ways in which Pennant's final acceptance of his transatlantic heritage ties his work to other black British narratives written at the turn of the millennium, and places it within a cultural endeavour to re-imagine Britain as a multicultural space and experience.